PENGARUH PEMBERIAN OLAHAN JANTUNG PISANG TERHADAP KELANCARAN AIR SUSU IBU (ASI) PADA IBU POST PARTUM - Syahroni Damanik; Pratiwi Nasution; May Frinsiska Siahaan (LPPM Universitas Abdurrab, 2025)
Introduction; Breast milk is the best food for babies, but according to the World Health Organization (WHO) in 2023, global coverage of exclusive breast milk is recorded at 44%, this is because the mother's breast milk does not come out, so it is necessary to give food that is high in lactogogum, such as processed banana blossoms. Banana blossoms have high levels of nutrients that can meet nutritional needs and influence breast milk adequacy, so that the breastfeeding period goes smoothly. Objective: determine the effect of providing processed banana flower to the smooth production of breast milk in postpartum mothers at Lasmi Kartika Clinic, Tanah Tinggi Village. Method; The is quasi-experimental research that was conducted at clinic in July 2024. The population was 15 post partum mothers. The sample used purposive sampling as many as 10 people. Data analysis using univariate and bivariate with paired t test. Result; The findings showed that the majority of respondents aged 20-35 years were 7 individuals (70%), 8 people (80%), and 10 people (100%), respectively. The average smoothness of breast milk before providing processed banana flower 31.5 ml, while the average smoothness of breast milk after giving processed banana floweri 71.5 mL. The paired t test resulted in a sig value of 0.001 < 0.05.. Conclusion; The study concluded that giving processed banana heart had an influence on the smoothness of breast milkin postpartum mothers at Lasmi Kartika Clinic, Tanah Tinggi Village and mothers are expected to consume processed banana blossoms.